Por uma reforma agrária baseada na soberania alimentar: a superação de obstáculos ecossocioeconômicos para mitigação da insegurança alimentar e nutricional no Brasil - Garcez, Thaymara Rodrigues (2024)
The agricultural sector in Brazil is characterized by the concentration of land destined for monoculture agricultural production for export. This "commoditization" of the countryside requires the implementation of an agrarian reform that effectively promotes access to rural property, social justice, and national economic development, ensuring the appropriate use of land, which is, above all, a provider of food and income. Therefore, the main objective of this dissertation is to identify the obstacles and ways to overcome them to promote food and nutritional security through agrarian reform, aiming for food sovereignty in Brazil. Specifically, the aim is to understand the eco-socioeconomic challenges for the implementation of agrarian reform; to establish levels of food security based on two elements: availability, access, utilization, and stability; and, finally, to identify ways, through agrarian reform and ancillary public policies, to raise these levels to achieve food sovereignty. This research is justified by the need to address the agricultural issue as a social development policy through structural reforms aimed at ultimately shaping it. From a methodological standpoint, this is normativelegal research; it uses inductive and deductive data collection methods; and qualitative techniques, with primary and secondary research sources. The dissertation's first chapter identifies the existing eco-socioeconomic obstacles to mitigating food and nutritional security in Brazil. The second chapter defines the levels of implementation of food sovereignty based on agrarian reform. The third chapter establishes measures to overcome each level of food insecurity based on eco-socioeconomic measures. The analysis revealed a high concentration of financial resources; incentives for monoculture for export; and the lack of adoption of ancillary public policies aimed at promoting family farming as social obstacles. As ecological obstacles, we highlight the inefficiency of land expropriation due to failure to fulfill the socioenvironmental function and the lack of public policies to support family farming in the practice of sustainable agriculture. As economic obstacles, we highlight the control of productive capital by financial capital and dependence on the external market. The research results demonstrate that agrarian reform promotes family farming combined with ancillary public policies; that it enables the fulfillment of the socio-environmental function of property and policies of cooperation with environmental services, recognizing the multifunctionality of agriculture; and that it separates productive capital from finance, demonstrating its capacity to build a nation that achieves food sovereignty, enabling stability and access to available and usable food.